Green Awareness Effects On Consumers' Purchasing Decision: Some Insights From Malaysia - Mohd. Suki, Norazah (Penerbit Universiti Sains Malaysia (USM Press), 2013)
Consumers' awareness on products marketed in green marketing is important in guiding their purchasing decision of green products. This study aims to examine the influence of consumers' environmental concerns, awareness of green product, price and brand image on their purchasing decision of green products. A total of 200 completed responses were collected in the survey. Responses were randomly drawn from students in a public university in the Federal Territory of Labuan, Malaysia. Their participation was purely voluntary.